A methods engineering study on FilWheels Inc. - Balanggao, Dedrick; Gumba, Chad Marcos; Maghari, Irish; Maula, Jennifer (College of Engineering, 2004)
Filwheels started the manufacture of light alloy wheels besides its automotive service shop in the late nineties under a single proprietorship of Mr. Rio Ceneda as a complimentary venture to his automotive service shop. After Filwheels gain acceptance in the market and was able to establish a dealership network mostly in Visayas and Mindanao, it incorporated and planned to bring the manufacturing section outside Metro Manila due to zoning constraints. Manufacturing facilities was then transferred completely to Teresa, Rizal late last year. Major problems encountered throughout this study may be classified into five major categories : (1) materials (2) plant layout and setup (3) equipment design (4) maintenance (5) work environment and workers' safety. One major concern is the arrival of Virgin Aluminum ingots. To sustain a continuous operation and high productivity, this primary ingredient should always be available in the plant. The primary solution generated to address this problem is Reordering point analysis (ROP). This simply requires past data of the company as basis. This study should be started once the proposal is approved for immediate implementation of a more effective and efficient ordering system. Other concerns deal closely with the flow of operations inthe plant. Cases of backtracking and long moves were observed in the foundry and finishing area. Raw materials are not easily accessible due to lack of proper storage. This scenario also induces contamination, which may interfere in the following operations. Setup of tools in the foundry and finishing area do not aid in a smooth flow of operations. Tools are not positioned to be accessed as quickly as possible, thus inducing delays. The platform truck used in moving alloy wheels in the plant also cause delays since wooden racks should be arranged each time wheels need to be moved. It also increases space requirements in each work station. Some proposals regarding plant layout are generated. In the foundry, the main feature is to interchange the position of casting machine and melting furnace to eliminate backtracking and long moves. The proposed layout also requires positioning of shovels, scoops, and other tools near the station they are intended for. Storage for raw materials is also designed for accessibility. Storage bins are required for protection of raw materials. Estimated cost for these modifications in the foundry adds up to P33,000. Duration of implementation may last up to one wee due to some construction works required. In the finishing area, it is recommended to interchange the location of valve hole drilling machine and leak test machine. A modified primer sanding booth with sandpaper rack is also suggested to eliminate travel time in obtaining sandpapers. Since modifications are simple, it may be implemented at a low cost of P2,000. It only requires some sort of labor. Supplies needed are mostly salvaged materials. Moreover, it will only take at most one day to implement this modified layout. A new hand truck is also recommended. The proposed design is made to fit the worker in terms of physical body features. It also promotes a more efficient way of material handling in the plant. Salvaged materials may be used to construct new trucks. It may take two days to finish construction of the trucks. Another cause of interruption in operations is machine breakdown. One way to prevent this scenario is to conduct periodic inspection of machines. Another concern is the condition of work environment. This is closely related with worker's health and safety. In the foundry, lighting and ventilation is a major problem. To address these concerns, installation of transparent roofing and wind driven rotary ventilators is recommended. Estimated costs are P13,000 for transparent roofing and P214250 for ventilators. It is recommended to install these proposals simultaneously with the new foundry layout. To ensure safety if workers, strict policies on the use of safety gadgets should be implemented. This should be done immediately after this proposal is approved. All recommendations generated in this study aims to improve productivity of the company in order for them to accommodate more orders. The problems identified imply wasted opportunities in terms of profitability. The proposed solutions may help the company to operate at least near its full potential.